Eelgrass (Zostera marina) leaf shoot densities and plant sizes in natural and transplanted meadows at three sites in Kieler Bucht, Baltic Sea - Tadhg O extquotesingleCorcora; Maike Paul; Mareike Taphorn; Lars Kamperdicks; Robin-Macmahon Bähre; Hannah Behnsen; Hans-Josef Endres; Andrea Wunsch; Lennard Kröger; Wilfried Rickels; Angela Stevenson; Jana Willim; et al. (PANGAEA, 2025)
This dataset contains plant density and plant attributes in eelgrass (Zostera marina) meadows that were restored during the BMBF-SeaStore project compared to natural donor meadows over time. Restoration took place at three sites in the Southwestern Baltic Sea in 2021 (Kieler Förde and Maasholm) and in 2022 (Geltinger Bucht). Two donor beds (Kieler Förde for both, Kieler Förde and Maasholm; and Gelting Donor for Geltinger Bucht) served as source for the transplanted leaf shoots which were planted using the single shoot technique via SCUBA diving without any special anchoring. Planting took place in a 1x1-m checkerboard pattern of 16 x 16 m in total (N=4 per site), in half the checkerboards a density of 8 leaf shoots per m2 was applied and in the other half 16 leaf shoots per m2 was used. Leaf shoot densities were only measured in planted quadrats of 1x1m. The donor meadows were also assessed for signs of damage due to the removal of a maximum of 2% of leaf shoots (comparison donor_pristine vs. donor_harvest). Hapharazdly selected plants were measured for total size (sediment to tip of longest leaves). For the donor area, the corner coordinates of the sampling rectangle are specified.